Nomograms to predict naming decline after temporal lobe surgery in adults with epilepsy. (4th December 2018) - Busch, Robyn M.; Hogue, Olivia; Kattan, Michael W.; Hamberger, Marla; Drane, Daniel L.; Hermann, Bruce; Kim, Michelle; Ferguson, Lisa; Bingaman, William; Gonzalez-Martinez, Jorge; Najm, Imad M.; Jehi, Lara
Abstract : Objective: To develop and externally validate models to predict the probability of postoperative naming decline in adults following temporal lobe epilepsy surgery using easily accessible preoperative clinical predictors. Methods: In this retrospective, prediction model development study, multivariable models were developed in a cohort of 719 patients who underwent temporal lobe epilepsy surgery at Cleveland Clinic and externally validated in a cohort of 138 patients who underwent temporal lobe surgery at one of 3 epilepsy surgery centers in the United States (Columbia University Medical Center, Emory University School of Medicine, University of Washington School of Medicine). Results: The development cohort was 54% female with an average age at surgery of 36 years (SD 12). Twenty-six percent of this cohort experienced clinically relevant postoperative naming decline. The model included 5 variables: side of surgery, age at epilepsy onset, age at surgery, sex, and education. When applied to the external validation cohort, the model performed very well, with excellent calibration and a c statistic (reflecting discriminatory ability) of 0.81. A second model predicting moderate to severe postoperative naming decline included 3 variables: side of surgery, age at epilepsy onset, and preoperative naming score. This model generated a c statistic of 0.84 in the external validation cohort and showed good calibration. Conclusion: Externally validated nomograms are provided in 2 easy-to-use formats (paper version and online calculator) clinicians can use to estimate the probability of naming decline in patients considering epilepsy surgery for treatment of pharmacoresistant temporal lobe epilepsy.